Peningkatan Motivasi dan Keterampilan Menulis Drama Berbahasa Jawa dengan Model CTL Berbantuan Media Audiovisual - Geni Purbatini (Universitas Pancasakti Tegal, 2017)
This research was aimed to increase motivation and writing skill of Javanese script’s students at XII IPA 3 SMA Negeri 1 Kramat, 2016/2017 academic years. This research was conduct in two circle using Contextual Teaching and Learning (CTL) strategy by audiovisual media. From the result of the research there was the rise of student’s learning motivation from the average 68,1 % in the first circle become 86,9 % in the second circle. Whereas the result of learning in writing drama script from 75 % in the first circle become 93,8 % in the second circle. It is proved that the use of CTL strategy by audiovisual media can increase student’s motivation and students’ writing skill of Javanese drama script